Development of dental material glass ionomer cement removal technique using ND:YAG laser / Noorsyazwani Zulkifli - Noorsyazwani , Zulkifli (2019)
Laser glass ionomer cement (GIC) removal is identified as an ideal technology to replace conventional technique in GIC removal process. The traditional method in GIC removal will lead to soft tissue inflammation, gingival bleeding, and crestal bone loss. A unique characteristics of laser technique such as versatile, precise, and controllable will overcome these problems. The purpose of this research is to develop a new method that suitable for removal GIC dental materials for clinical purpose. Nd: YAG laser (Spectron Laser System, SL-805G, USA) with maximum energy of 200 mJ and 1064 nm wavelength was investigated. There were 147 of GIC tooth sample had been irradiated. The irradiated samples were proceeded to surface texture analysis, surface morphology analysis and elemental composition determination by using surfcom 130A, scanning electron microscopy and energy dispersive x-ray. The study concludes the efficiency of GIC removal was increased as the laser energy increase. In addition, the influence of repetition rate of laser parameters was significant in GIC removal process. The research also concludes the laser GIC removal techniques was considered safe compared to the traditional method. Optimum operational process for GIC tooth dental material was set up with 200 mJ laser energy, 10 number of shots, 0.17 Hz repetition rate and 0.5 mm laser beam size. Thus, the study proved the effectiveness, quality and efficiency of GIC removal process can be obtained with the proper selection of parameters of this Nd:YAG laser.